Facing Climate Change: Application of Microbial Biostimulants to Mitigate Stress in Horticultural Crops - Sangiorgio, Daniela; Cellini, Antonio; Donati, Irene; Pastore, Chiara; Onofrietti, Claudia; Spinelli, Francesco (Agronomy (Basel), 2020)
In the current scenario of rapidly evolving climate change, crop plants are more frequently subjected to stresses of both abiotic and biotic origin, including exposure to unpredictable and extreme climatic events, changes in plant physiology, growing season and phytosanitary hazard, and increased losses up to 30% and 50% in global agricultural productions. Plants coevolved with microbial symbionts, which are involved in major functions both at the ecosystem and plant level. The use of microbial biostimulants, by exploiting this symbiotic interaction, represents a sustainable strategy to increase plant performances and productivity, even under stresses due to climate changes. Microbial biostimulants include beneficial fungi, yeasts and eubacteria sharing the ability to improve plant nutrition, growth, productivity and stress tolerance. This work reports the current knowledge on microbial biostimulants and provides a critical review on their possible use to mitigate the biotic and abiotic stresses caused by climate changes. Currently, available products often provide a general amelioration of cultural conditions, but their action mechanisms are largely undetermined and their effects often unreliable. Future research may lead to more specifically targeted products, based on the characterization of plant-microbe and microbial community interactions.